Prediction of body fat through body adiposity index and bioelectrical impedance analysis in a sample of physically active Mexican students - Ochoa Martínez, Paulina Yesica (2018)
Objective: To compare the body fat percentage %BF predicted through the body adiposity index (BAI) BAI in a sample of physically active Mexican college students, using bioelectrical impedance analysis (BIA) as reference method. Methods: 78 volunteered university students (20.67 ± 1.69 yrs.) partake in study considered as highly active; the %BF determined by BIA was performed using Inbody 720; BAI was calculated by anthropometric assessment from hip and height measures calculated as follows: BAI=[hip circumference (cm)/height (m)1.5]–18. Pearson’s correlation coefficient was used to evaluate the association between BAI and %BF assessed by BIA. Results: The correlations of % BF between BIA and the estimated by BAI were r = 0.81, p < 0.001 in man and r = 0.69, p < 0.001 in women. Paired t-test in man showed a significant mean difference in %BF between methods (p = 0.001). The bias of the body adiposity was 5.77± 4.2 % (CI95% = 4.40 to 7.14), indicating that the body adiposity index method measured lower %BF than the bioelectrical impedance. Paired t-test in women did not show significant difference (p = 0.355). Lin’s concordance correlation coefficient was considered poor in man (ρc = 0.49) and women (ρc = 0.63), indicating than BAI underestimating %BF in relation to the BIA. Conclusion: In physically active Mexican college students, BAI presented low agreement with %BF measured by BIA; therefore, BAI is not recommended for %BF prediction in this sample studied.